2019
DOI: 10.1037/neu0000510
|View full text |Cite
|
Sign up to set email alerts
|

Executive function, impulsivity, and risky behaviors in young adults.

Abstract: Objective: Among patients with brain damage, executive function deficits and impulsivity correspond with propensity to engage in risky behaviors. Less research has addressed this issue in healthy adults, and fewer still have simultaneously evaluated the importance of executive function and impulsive personality. Additionally, most research has focused exclusively on substance use while ignoring other domains of risky behavior such as sexual activity and antisocial practices. Toward this end, we examined the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 96 publications
3
56
0
2
Order By: Relevance
“…2 Scatterplots of performance to the visual attention task in the total delta, theta, alpha, and beta bands (raw data) increase dramatically. In the life of each person, executive functions have a crucial role in adaptive functioning, with consequent effects on quality of life, and recent research indicated executive dysfunctions as the core problem of some psychiatric conditions [72][73][74][75]. Furthermore, executive deficits are a frequent report after premature birth [76].…”
Section: Discussionmentioning
confidence: 99%
“…2 Scatterplots of performance to the visual attention task in the total delta, theta, alpha, and beta bands (raw data) increase dramatically. In the life of each person, executive functions have a crucial role in adaptive functioning, with consequent effects on quality of life, and recent research indicated executive dysfunctions as the core problem of some psychiatric conditions [72][73][74][75]. Furthermore, executive deficits are a frequent report after premature birth [76].…”
Section: Discussionmentioning
confidence: 99%
“…Also, high-risk behaviors are characterized by dysfunction of attentional processes. Individuals with high-risk behaviors pay attention only to affect-eliciting events (winning and losing); therefore, they are not able to learn from their mistakes ( 59 ). Moreover, decision-making difficulty in individuals with ventromedial prefrontal cortex lesions is related to blindness to the results and consequences of future actions (more immediate profit and fewer harm).…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is an important characteristic, since impulsivity is an important aspect of obsessive-compulsive disorder (OCD) and attention deficit hyperactivity disorder (ADHD) [53][54][55]. We should also bear in mind that poor executive function increases the likelihood that healthy young adults will engage in risky and potentially dangerous acts [56]. Unfortunately, we cannot avoid the fact that the pandemic will be traumatic for children, and a history of childhood trauma in OCD patients has indirect effects on the severity of the OCD and depressive symptoms and is associated with more severe anxiety, higher levels of impulsivity, a higher prevalence of ADHD and lower levels of education [57].…”
Section: Plos Onementioning
confidence: 99%